The preventive effects of ondansetron on chemotherapy-induced nausea and vomiting in adult cancer patients: systematic review from ClinicalTrials.gov - Ashour, Ahmed M. (Frontiers in Pharmacology, 2023)
Cancer is a neoplastic transformation that affects tissue. Among the many complications associated with cancer treatment, managing the distressing side effects of chemotherapy-induced nausea and vomiting (CINV) is of main concern. Ondansetron is a selective serotonin 5-HT3 receptor antagonist that has emerged as an essential medication against CINV in adult cancer patients. Ondansetron efficacy and tolerability have made it a primary medication in CINV prophylaxis and treatment regimens. The study aims to offer a detailed overview of ondansetron's effectiveness, safety, and impact on patients' lives, ultimately contributing to the ongoing research to enhance the quality of cancer care.Methods: On September 4th, 2023, a search was conducted of the ClinicalTrials.gov database using the search terms "cancer," "ondansetron," and "Zofran." Inclusion and exclusion criteria were defined to select relevant clinical trials. Included trials were completed with results and interventional studies that assessed the preventive effects of ondansetron on CINV in adult cancer patients.Results: A total of 23 clinical trials were identified, with only 13 of them focusing on investigating the preventive effects of ondansetron on CINV in adult cancer patients. The collective findings from these trials showed an effective management of CINV using ondansetron.Through a comprehensive overview of clinical trials, the use of ondansetron in adult cancer patients represents a significant improvement in CINV management.